An Integrated Framework for the Architectural Evaluation of the Identity of Qajar Houses - Farahbod, Amir Reza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Throughout the history of architecture in Iran, the term identity has been changed due to the dynamic and temporal aspects shaping the identity of architecture. Mainly, during the Qajar period (1795-1925) due to social, political, and economic changes, there was a sharp milestone from the vernacular approach of design to more contemporary approaches of construction which led to the development of a specific identity in architecture of houses in Qajar period. In this regard, this study aims to develop an integrated framework to assess the identity of Qajar houses. The methodology developed in this study is mainly qualitative assessment based on content analysis and case studies. Historical analysis has been used to assess as applicable technique on the case studies in Qajar period. Overall, the methodology in this qualitative grounded theory study will be classified into three main parts: a) Discourse and content analysis b) Historical analysis c) Site survey. Accordingly, indicators shaping the identity of architecture have been classified into seven main groups and further developed based on static and dynamic organization which shapes the identity of traditional Iranian architecture. The study also revealed that in Qajar period, there is a possibility of classifying the identity of architecture into three main periods. Overall, it reveals that the amalgamation of the dynamic and static factors shaping identity is the most important factor that forms the identity of Qajar houses. Generally, it concludes that apart from radical social, political, economic and technological changes in the Qajar period, some traditional principles of housing (such as courtyards, simplicity in design) are frozen, but culture - architecture- of privacy in design due to the people’s religion is continuing. Keywords: Identity; Traditional Iranian Houses; Transition period; Qajar period.

ÖZ: Mimari kimliği şekillendiren dinamik ve zamansal değişim etkenlerinden dolayı mimarlık tarihi boyunca İran mimarisine yönelik “kimlik” terimi, sürekli değişim göstermiştir. Özellikle sosyal, ekonomik, politik değişiklikler nedeniyle Qajar döneminin (1795-1925) geleneksel tasarım yaklaşımından, çağdaş inşaat yaklaşımlarına dönüşmesi ve mimaride belirli bir kimliği geliştirmeye yön veren keskin bir kilometre taşı olması, o dönemde konut mimarisinde özgün bir kimlik oluşumunun ortaya çıkmasına neden olmuştur. Bu bağlamda tez, Qajar evlerinin kimliğini değerlendirmek için bütünleşik bir çerçeve geliştirmeyi amaçlamıştır. Çerçeveyi ortaya koyabilmek için Geleneksel İran Evlerinin tarihsel değerlendirmesine dayanan içerik analizi ve mimari kimliğe yönelik literatür çalışması ile nitel değerlendirme, yöntem olarak kullanılmıştır. Tez kapsamında mimari kimliği şekillendiren göstergeler, yedi ana gruba (Zamansal Değişiklikler, Semantik İlişki, Mekânsal Organizasyon, Genel Tasarım İlkeleri, Şekil ve Biçim, Yapı Malzemeleri, Bağlamla İlişki) ayrılmış ve geleneksel mimarinin kimliğini şekillendiren statik ve dinamik organizasyona dayalı olarak da geliştirilmiştir. Tez, Qajar dönemi mimari kimliğinin birinci, ikinci ve üçüncü olmak üzere üç ana dönemde sınıflandırılması yaklaşımını ve genel olarak kimliği şekillendiren dinamik ve statik faktörlerin birleşiminin Qajar evlerinin kimliğini oluşturan en önemli faktör olduğunu, ortaya koymuştur. Sonuç olarak Qajar döneminde sosyal, politik, ekonomik ve teknolojik anlamda yaşanan radikal değişimlerin yanı sıra iç avlu ve sadelik gibi konut tasarımındaki bazı geleneksel prensipler dondurulmuş ayrıca, insanların dini inançlarından dolayı kültürün ana elemanı olan mahremiyet, tasarımlarda devam etmiştir. Anahtar Kelimeler: Kimlik, Geleneksel İran Evleri, Geçiş Dönemi, Qajar Dönemi
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2018. Supervisor: Prof. Dr. Uğur Ulaş Dağlı.
Keywords: Architecture; Architecture and Design--Qajar--Iran; Housing--Qajar Houses--Iran; Vernacular architecture--Iran; Islamic architecture--Iran; Identity; Traditional Iranian Houses; Transition period; Qajar period